Seasonal Distribution and Relative Abundance of Fish Fauna of a Small Hill-Stream Dangchaura (Takoli) Gad, along with River Alaknanda - Bisht, B.; Badoni, A.K.; Bahuguna, S.N. (Our Nature, 2010)
The present study was carried out to investigate seasonal distribution and relative abundance of fish fauna of a small hill stream Dangchaura (Takoli) Gad along with river Alaknanda. The differences in availability of fish-fauna were directly related to the nature of profile and slope of tributary; which affects the migration and breeding grounds of the fishes inhabited in the main river Alaknanda. Key words: Hill-stream fish fauna, Seasonal distribution, Dangchaura Gad DOI: 10.3126/on.v7i1.2569 Our Nature (2009) 7:182-186